2018
DOI: 10.1021/acs.jctc.7b00602
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Energy Landscapes of Aromatic Heterocycles through a Reliable yet Affordable Computational Approach

Abstract: Noncovalent interactions between homodimers of several aromatic heterocycles (pyrrole, furan, thiophene, pyridine, pyridazine, pyrimidine, and pyrazine) are investigated at the ab initio level, employing the Möller-Plesset second-order perturbation theory, coupled with small Gaussian basis sets (6-31G* and 6-31G**) with specifically tuned polarization exponents. The latter are modified using a systematic and automated procedure, the MP2 approach, based on a comparison with high level CCSD(T) calculations extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(65 citation statements)
references
References 93 publications
2
63
0
Order By: Relevance
“…Moreover, the second-order Møller–Plesset (MP2) perturbation theory is computationally less expensive (compared with CCSD(T)), but its accuracy is reported to be dependent on the type of basis set used. 39 Hobza et al suggested the use of the MP2/cc-pVTZ level of theory for this purpose, which would also be prohibitively expensive for the considered systems. 40 DFT methods are computationally more convenient than CCSD(T) and MP2 calculations and hence, in this study, DFT functionals are used.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the second-order Møller–Plesset (MP2) perturbation theory is computationally less expensive (compared with CCSD(T)), but its accuracy is reported to be dependent on the type of basis set used. 39 Hobza et al suggested the use of the MP2/cc-pVTZ level of theory for this purpose, which would also be prohibitively expensive for the considered systems. 40 DFT methods are computationally more convenient than CCSD(T) and MP2 calculations and hence, in this study, DFT functionals are used.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Jacobs et al have also suggested the importance of a suitable DFT functional and basis set for estimating the noncovalent interactions. 39…”
Section: Results and Discussionmentioning
confidence: 99%
“…Quantum chemical methods are popularly used to understand different aspects of noncovalent interactions. CCSD(T) (coupled cluster theory with perturbative triples) and MP2 (second order Moller‐Plesset) approaches are generally used for accurate estimation of weaker interactions . CCSD(T) calculation in association with complete basis set limit (CBS) is known to be gold standard in quantum chemistry .…”
Section: Computational Detailsmentioning
confidence: 99%
“…Since, DFT methods are computationally more convenient than CCSD(T), therefore DFT functionals are used for the purpose. However, appropriate selection of functional (dispersion corrected) and basis set is important for accurate estimation of π⋯π stacking interactions . To find a suitable combination, two of the most common DFT functional viz.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, non‐covalent interaction arises from simultaneous contribution from different forces like electrostatic, exchange, induction, dispersion etc. However, nature of π⋯π stacking between two arene systems is documented to be primarily dispersive ,,. Apart from this, reports are also there which in favour of electrostatic interaction .…”
Section: Resultsmentioning
confidence: 99%